From understanding others' needs to prosocial action: Motor and social abilities promote infants' helping. Issue 6 (28th February 2019) - Köster, Moritz; Itakura, Shoji; Omori, Masaki; Kärtner, Joscha
Abstract: In the present study, we test the main hypothesis that infants' understanding of others' needs translates into helping behavior, when critical motor and social competencies have emerged, early in the second year. We assessed the understanding of others' needs in an eye‐tracking paradigm and the helping behavior of 10‐ ( n  =   41) and 16‐month‐olds ( n  =   37). Furthermore, we assessed the motor and social abilities of 16‐month‐olds. Critically, while infants understood others' needs already at 10 months, fine motor and social interaction skills moderated the link between infants' prosocial understanding and helping behavior at 16 months. This provides first evidence that infants' helping behavior relates to their understanding of others' needs. Furthermore, we found that fine motor, gross motor, and social interaction skills predicted early helping behavior by themselves. These findings highlight that the emergence of infants' helping behavior is the result of a developmental system that includes infants' understanding of others' needs and also their motor and social competencies. The link between infants' understanding of others' needs and their early helpful actions provide further support for the prosocial nature of early helping behavior. Abstract : Fine motor and social interaction skills moderated the link between infants' prosocial understanding and helping behavior. The emergence of infants' helping behavior is the result of a developmental system that includes infants' understanding of others' needs and also their motor and social competencies. The link between infants' understanding of others' needs and their early helpful actions supports the prosocial nature of early helping behavior.